The Effectiveness of Utilizing Chromebook Facilities as Learning Media at Pulias Abaling Elementary School - Nasriani (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to find out how effective the use of chromebooks is as a learning medium at SD Negeri Pulias Abaling, Ogodeide District, Tolitoli Regency. This type of research used a descriptive qualitative approach. The research subjects were teachers and fifth grade students at SD Negeri Pulias Abaling. The data collection techniques used were observation, interview and documentation techniques with instruments in the form of observation sheets to obtain activity data of educators and students, interview sheets and documentation. Data analysis techniques are data reduction, presenting research data and verifying or concluding research results. In this study it was found that the achievement of learning completeness had been achieved, the effectiveness of student activities was achieved, the effectiveness of teacher activities managing learning had been achieved and student responses to positive learning had been achieved. The conclusion in this study is that the effectiveness of the Chromebook as a learning medium for fifth grade students at SD Negeri Pulias Abaling is implemented effectively